Ateisme Masa Kini: Sebuah Catatan Singkat Julian Baggini - Muhammad, Iqtamar (Inklusiva: Jurnal Studi Agama-Agama, 2025)
This article discusses about Julian Baggini's views on atheism using the literature research method and is an argumentative and reflective qualitative research. This article seeks to explain Julian Baggini's atheism, which provides philosophical insight and foundation in recognizing atheism comprehensively. Then, the atheism explained by Julian Baggini has an attempt to explore atheism empirically and academically. Moreover, this article also seeks to explore the distinctive claims of atheism. Julian Baggini says that atheism is the belief that there is no God or gods. Atheism, however, is intrinsically negative in terms of belief in God. Moreover, atheism is capable of having a positive outlook on other aspects of life, just like the concept of theism. Julian Baggini's idea of atheism is not only applicable to the modern era, but also, can apply to the contemporary era even in the post-truth era, where truth is widely spread and diverse, including truths that are considered eternal and divine.